2011
DOI: 10.1002/ca.21287
|View full text |Cite
|
Sign up to set email alerts
|

A four trunked brachial plexus and a post fixed brachial plexus: A conjunction or a co‐incidence?: Report of three cases

Abstract: The anatomical variations of the brachial plexus in humans have clinical significance for surgeons, radiologists, and anatomists. In a study of 60 brachial plexuses, four trunked brachial plexuses were encountered in three limbs (two female and one male), all of them being post fixed and on left side of cadavers. The third trunk in all these limbs gave rise to two anterior divisions (upper and lower) and one posterior division. In two limbs belonging to the female sex, the upper anterior division joined with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 12 publications
1
7
0
1
Order By: Relevance
“…The first trunk was formed by the union of C5 and C6 (Trunk I) and the second, third and fourth trunks were a continuation of C7, C8 and T1 roots respectively. A similar finding was also described by Chaudhary, Singla, Kalsey et al (2012), although differing with regard to the divisions for the formation of lateral, medial and posterior cords.…”
Section: Resultssupporting
confidence: 85%
“…The first trunk was formed by the union of C5 and C6 (Trunk I) and the second, third and fourth trunks were a continuation of C7, C8 and T1 roots respectively. A similar finding was also described by Chaudhary, Singla, Kalsey et al (2012), although differing with regard to the divisions for the formation of lateral, medial and posterior cords.…”
Section: Resultssupporting
confidence: 85%
“…Almost 50% of the BP showed variability in their branching pattern [2]. Anomalies of the cords and terminal branches of BP have been well documented [8,10,25]; however, anomalies of the roots and trunks are comparatively rare and have been report- ed in only a few cases [4,11,25]. BP variants are of immense importance during surgery of the axilla and arm region and during nerve blockade.…”
Section: Introductionmentioning
confidence: 99%
“…There are very few reports in the scientific literature addressing cases of BP with four trunks. Investigating 60 BPs which belonged to 30 cadavers, Chaudhary et al 10 found four trunked brachial plexuses on the left side in three cases. Of the three cases, one BP (prefixed and postfixed) was composed of roots C4-T2 which formed four trunks: first trunk (C4-C6), second trunk (C7), third trunk (C8), and fourth trunk (T1 and T2).…”
Section: Discussionmentioning
confidence: 99%